Chromium ion doped phosphate photoluminescent material as well as preparation method and application thereof
Through the preparation of chromium ion-doped phosphate photoluminescent materials, the problem of insufficient wavelength and frequency band of photoluminescent materials is solved, and the moisture content in organic solvents is used to detect the rapid and non-contact detection method, which is suitable for multiple application areas.
Patent Information
- Application Number
- CN202411579706.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-07
AI Technical Summary
Existing photoluminescent materials are not wide enough under blue light excitation, making it difficult to cover the absorption bands of C-H bonds and O-H bonds. In addition, the detection of trace moisture in organic solvents lacks fast, non-contact and lossless methods, which affects product quality and equipment. life.
Using chromium ion doped phosphate photoluminescent material, the chemical structure is CaHf4-x(PO4)6:xCr3+, prepared by mixing and calculating calcium, hafnium, ammonium dihydrogen phosphate and chromium-containing compounds to prepare long wavelengths and broadband near-infrared emission materials and used to detect moisture content in organic solvents.
It realizes near-infrared emission of long wavelength and wide bands under blue light excitation, is suitable for night vision lighting, food detection and medical imaging, and provides a fast, non-contact and non-destructive detection method, simplifying the material preparation process.
Smart Images

Figure CN119286518A_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a luminescent material, and also discloses a preparation method and application of the chromium ion-doped phosphate photoluminescent material, belonging to the technical field of inorganic photoluminescent materials. Background Art
[0002] Photoluminescent materials refer to materials that can absorb light energy of a specific wavelength and re-emit photons of different wavelengths through a radiation process. The photoluminescence phenomenon usually involves the process of electrons transitioning from the ground state to the excited state and then releasing energy when returning to the ground state. Due to their unique optical properties, photoluminescent materials have broad application prospects in many fields such as night vision lighting, medical imaging, biological tissue analysis, industrial detection, plant growth, etc. With the continuous deepening of research, although significant progress has been made in the field of photoluminescent materials, there are still many challenges. For example, how to improve the quantum yield of the material, broaden the luminescent wavelength range, enhance environmental stability, and simplify the preparation process. In addition, in order to meet the needs of specific applications, the development of new photoluminescent materials with special properties remains a research hotspot.
[0003] In the chemical industry, there are often trace amounts of water in some organic solvents, which can have a significant impact on the production process. The presence of trace amounts of water in the organic solution as a raw material will not only reduce the purity of the product, affecting product quality and performance, but may also cause side reactions and produce impurities, reducing reaction efficiency and yield. In addition, moisture can cause corrosion of equipment, affect the life of the equipment, increase maintenance costs and safety risks. Therefore, in order to reduce the impact of trace amounts of water in organic solvents, it is necessary to perform faster and more accurate testing of the purity of the solvent, and to implement it in all aspects of production and storage and transportation. At present, there is a lack of a fast, non-contact and non-destructive detection system for the detection of trace amounts of water in organic solvents, which can accurately determine the moisture content and provide timely feedback to control the production process. Summary of the invention
[0004] In view of the above problems, the technical problem to be solved by the present invention is to provide a new type of chromium ion-doped phosphate photoluminescent material, which can produce long-wavelength and broadband near-infrared emission under blue light excitation, covering the CH bond absorption band (908nm) and the OH bond absorption band (980nm).
[0005] The second technical problem to be solved by the present invention is to provide a novel method for preparing a chromium ion-doped phosphate photoluminescent material. The preparation method is relatively simple to operate and environmentally friendly, making the chromium ion-doped phosphate photoluminescent material easy to prepare on a large scale.
[0006] The third technical problem provided by the present invention is to use the above-mentioned chromium ion-doped phosphate photoluminescent material to judge the water content in an organic solvent, so as to achieve rapid, non-contact and non-destructive judgment of the water content in the organic solvent.
[0007] To this end, the first technical solution provided by the present invention is as follows:
[0008] A chromium ion doped phosphate photoluminescent material, the chemical formula is CaHf 4-x (PO4)6:xCr 3+ , 0<x≤0.09.
[0009] The second technical solution provided by the present invention is a method for preparing the above-mentioned chromium ion-doped phosphate photoluminescent material, which comprises the following steps in sequence: mixing a calcium-containing compound, a hafnium-containing compound, ammonium dihydrogen phosphate and a chromium-containing compound, calcining them at 1150° C. to 1350° C. for 4 h to 6 h in an air atmosphere, and grinding the calcined product after natural cooling to obtain the chromium ion-doped phosphate photoluminescent material.
[0010] The molar ratio of the calcium-containing compound, the hafnium-containing compound, the ammonium dihydrogen phosphate and the chromium-containing compound is 1:3.91-3.99:6:0.01-0.09.
[0011] Furthermore, in the above-mentioned method for preparing a chromium ion-doped phosphate photoluminescent material, the calcination temperature is 1230°C to 1280°C.
[0012] Furthermore, in the above-mentioned method for preparing a chromium ion-doped phosphate photoluminescent material, the calcination time is 5 hours.
[0013] Furthermore, in the above-mentioned method for preparing a chromium ion-doped phosphate photoluminescent material, the molar ratio of the calcium-containing compound, the hafnium-containing compound, the diammonium phosphate, and the chromium-containing compound is 1:3.95-3.99:6:0.03-0.07.
[0014] Furthermore, in the above-mentioned method for preparing a chromium ion-doped phosphate photoluminescent material, the calcium-containing compound is calcium carbonate; the hafnium-containing compound is hafnium oxide; and the chromium-containing compound is chromium oxide.
[0015] Furthermore, the above-mentioned method for preparing a chromium ion-doped phosphate photoluminescent material, after mixing the calcium-containing compound, the hafnium-containing compound, the ammonium dihydrogen phosphate and the chromium-containing compound, and before calcining in an air atmosphere, further comprises: grinding the mixture obtained by mixing the calcium-containing compound, the hafnium-containing compound, the ammonium dihydrogen phosphate and the chromium-containing compound to obtain a uniform mixed solid powder.
[0016] Furthermore, in the above-mentioned method for preparing a chromium ion-doped phosphate photoluminescent material, the calcination is performed at a heating rate of 5°C / min to 8°C / min, preferably at a heating rate of 6°C / min.
[0017] The last technical solution provided by the present invention is to use the above-mentioned chromium ion-doped phosphate photoluminescent material to detect the water content in an organic solvent.
[0018] The present invention also provides a phosphor-converted LED of a luminescent material, wherein epoxy resin and the CaHf according to claim 1 are weighed in a mass ratio of 2:1. 3.95 (PO4)6:0.05Cr 3+ The compound was placed in a stirrer and mixed for 10 minutes to obtain a uniform phosphor silica gel mixture; the obtained mixture was evenly coated on the surface of the blue light LED chip with a dispenser, the coated blue light LED chip was placed in an oven, the temperature was increased to 100°C at a heating rate of 2°C / min, and the mixture was kept warm for 1 hour in an air atmosphere for curing, and after cooling to room temperature, a CaHf 3.95 (PO4)6:0.05Cr 3+ Phosphor conversion LED with compound as luminescent material.
[0019] Compared with the prior art, the technical solution provided by the present invention has the following technical advantages:
[0020] 1. The chromium ion-doped phosphate photoluminescent material provided by the present invention has good chemical stability and can produce long-wavelength and broadband near-infrared emission under blue light excitation. This photoluminescent property enables it to be well combined with blue light LED chips and used in the fields of night vision lighting, food testing and medical imaging.
[0021] 2. The novel method for preparing the chromium ion-doped phosphate photoluminescent material provided by the present invention is simple to operate and environmentally friendly, making the chromium ion-doped phosphate photoluminescent material easy to prepare on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The scanning electron microscope image of the chromium ion-doped phosphate photoluminescent material prepared in Example 1 of the present invention;
[0023] Figure 2 X-ray diffraction patterns of samples of chromium ion-doped phosphate photoluminescent material with different chromium ion doping concentrations prepared in Example 1 of the present invention;
[0024] Figure 3 The diffuse reflectance spectrum of the chromium ion-doped phosphate photoluminescent material prepared in Example 1 of the present invention under blue light excitation;
[0025] Figure 4 The fluorescence spectrum of the chromium ion-doped phosphate photoluminescent material prepared in Example 1 of the present invention under blue light excitation;
[0026] Figure 5 The near-infrared transmission spectra of methanol-water mixtures of different concentrations under the irradiation of the phosphor-converted LED prepared in Example 2 of the present invention;
[0027] Figure 6 The near-infrared transmission spectra of ethanol-water mixtures of different concentrations under the irradiation of the phosphor-converted LED prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] CaCO3, HfO2, NH4H2PO4 and Cr2O3 were weighed in a molar ratio of 1:3.95:6:0.05, and the mixture was thoroughly mixed and ground for 30 minutes to obtain a uniform mixed solid powder. The obtained mixed solid powder was placed in a corundum crucible, placed in a high-temperature furnace, heated to 500°C at a heating rate of 5°C / min, and kept warm for 2 hours in an air atmosphere for calcination. After the calcined product naturally cooled to room temperature, it was taken out and ground again. The mixed solid powder obtained after grinding was put into the corundum crucible again, covered and placed in a high-temperature furnace, heated to 1250°C at a heating rate of 6°C / min, and kept warm for 5 hours in an air atmosphere for calcination. After the calcined product naturally cooled to room temperature, it was taken out and ground again to obtain a chemical structure of CaHf 3.95 (PO4)6:0.05Cr 3+ Chromium ion-doped phosphate photoluminescent material.
[0031] See also Figure 1 and Figure 2 , respectively, are the scanning electron microscope images of the chromium ion-doped phosphate photoluminescent material prepared in Example 1 of the present invention and the X-ray diffraction patterns of samples of various concentrations. The results show that the chromium ion-doped phosphate photoluminescent material prepared in Example 1 has no additional X-ray diffraction peaks corresponding to impurities, and pure phase CaHf is successfully synthesized. 4-x (PO4)6:xCr 3+ Compound.
[0032] See also Figure 3 and Figure 4 , respectively, are the diffuse reflectance spectrum and fluorescence spectrum of the chromium ion doped phosphate photoluminescent material prepared in Example 1 of the present invention under blue light excitation. The results show that the chromium ion doped phosphate photoluminescent material prepared in Example 1 of the present invention has an absorption peak at 472nm and 720nm, respectively, and can generate long wavelength (914nm) and broadband (FWHM=160nm) near-infrared emission under light excitation with a wavelength of 472nm.
[0033] Example 2
[0034] CaCO3, HfO2, NH4H2PO4 and Cr2O3 were weighed in a molar ratio of 1:3.99:6:0.01, and the mixture was thoroughly mixed and ground for 30 minutes to obtain a uniform mixed solid powder. The obtained mixed solid powder was placed in a corundum crucible, placed in a high-temperature furnace, heated to 500°C at a heating rate of 5°C / min, and kept warm for 2 hours in an air atmosphere for calcination. After the calcined product naturally cooled to room temperature, it was taken out and ground again. The mixed solid powder obtained after grinding was put into the corundum crucible again, covered and placed in a high-temperature furnace, heated to 1150°C at a heating rate of 5°C / min, and kept warm for 6 hours in an air atmosphere for calcination. After the calcined product naturally cooled to room temperature, it was taken out and ground again to obtain a chemical structure of CaHf 3.99 (PO4)6:0.01Cr 3+ Chromium ion-doped phosphate photoluminescent material.
[0035] Example 3
[0036] CaCO3, HfO2, NH4H2PO4 and Cr2O3 were weighed in a molar ratio of 1:3.97:6:0.03, and the mixture was thoroughly mixed and ground for 30 minutes to obtain a uniform mixed solid powder. The obtained mixed solid powder was placed in a corundum crucible, placed in a high-temperature furnace, heated to 500°C at a heating rate of 5°C / min, and kept warm for 2 hours in an air atmosphere for calcination. After the calcined product naturally cooled to room temperature, it was taken out and ground again. The mixed solid powder obtained after grinding was put into the corundum crucible again, covered and placed in a high-temperature furnace, heated to 1230°C at a heating rate of 6°C / min, and kept warm for 5 hours in an air atmosphere for calcination. After the calcined product naturally cooled to room temperature, it was taken out and ground again to obtain a chemical structure of CaHf 3.97 (PO4)6:0.03Cr 3+ Chromium ion-doped phosphate photoluminescent material.
[0037] Example 4
[0038] CaCO3, HfO2, NH4H2PO4 and Cr2O3 were weighed in a molar ratio of 1:3.93:6:0.07, and the mixture was thoroughly mixed and ground for 30 minutes to obtain a uniform mixed solid powder. The obtained mixed solid powder was placed in a corundum crucible, placed in a high-temperature furnace, heated to 500°C at a heating rate of 5°C / min, and kept warm for 2 hours in an air atmosphere for calcination. After the calcined product naturally cooled to room temperature, it was taken out and ground again. The mixed solid powder obtained after grinding was put into the corundum crucible again, covered and placed in a high-temperature furnace, heated to 1280°C at a heating rate of 7°C / min, and kept warm for 5 hours in an air atmosphere for calcination. After the calcined product naturally cooled to room temperature, it was taken out and ground again to obtain a chemical structure of CaHf 3.93 (PO4)6:0.07Cr 3+ Chromium ion-doped phosphate photoluminescent material.
[0039] Example 5
[0040] CaCO3, HfO2, NH4H2PO4 and Cr2O3 were weighed in a molar ratio of 1:3.91:6:0.09, and the mixture was thoroughly mixed and ground for 30 minutes to obtain a uniform mixed solid powder. The obtained mixed solid powder was placed in a corundum crucible, placed in a high-temperature furnace, heated to 500°C at a heating rate of 5°C / min, and kept warm for 2 hours in an air atmosphere for calcination. After the calcined product naturally cooled to room temperature, it was taken out and ground again. The mixed solid powder obtained after grinding was put into the corundum crucible again, covered and placed in a high-temperature furnace, heated to 1350°C at a heating rate of 8°C / min, and kept warm for 4 hours in an air atmosphere for calcination. After the calcined product naturally cooled to room temperature, it was taken out and ground again to obtain a chemical structure of CaHf 3.91 (PO4)6:0.09Cr 3+ Chromium ion-doped phosphate photoluminescent material.
[0041] Example 6
[0042] Epoxy resin and CaHf prepared in Example 1 were weighed in a mass ratio of 2:1. 3.95 (PO4)6:0.05Cr 3+ The compound was placed in a stirrer and mixed thoroughly for 10 minutes to obtain a uniform phosphor silica gel mixture. The obtained mixture was evenly coated on the surface of the blue LED chip with a dispenser to ensure that the thickness of the phosphor layer was uniform. The coated blue LED chip was placed in an oven and heated to 100°C at a heating rate of 2°C / min. It was kept warm for 1 hour in an air atmosphere for curing. After cooling to room temperature, a CaHf 3.95 (PO4)6:0.05Cr 3+Phosphor conversion LED with compound as luminescent material.
[0043] The specific test method is as follows:
[0044] Use a 1 cm thick quartz cuvette to hold 1 ml of pure water, 1 ml of anhydrous methanol, and 1 ml of a methanol-water mixture with a concentration ratio of 2:8, 4:6, 6:4, and 8:2. Fix the phosphor conversion LED prepared in Example 6 in the straight line direction of the near-infrared probe, and sequentially place the quartz cuvettes filled with 1 ml of pure water, 1 ml of anhydrous methanol solution, and 1 ml of the methanol-water mixture with the above concentrations in the center axis of the phosphor conversion LED prepared in Example 6 and the near-infrared probe. Use a DC power supply to connect the phosphor conversion LED prepared in Example 6, turn on the power supply, and use the near-infrared probe to collect the transmitted light intensity, and collect the transmission spectrum as shown in the figure. Figure 5 shown.
[0045] Use a 1 cm thick quartz cuvette to respectively hold 1 ml of pure water, 1 ml of anhydrous ethanol, and 1 ml of an ethanol-water mixture with a concentration ratio of 2:8; 4:6; 6:4 and 8:2. Fix the phosphor conversion LED prepared in Example 6 in the straight line direction of the near-infrared probe, and sequentially place the quartz cuvettes filled with 1 ml of pure water, 1 ml of anhydrous ethanol solution, and 1 ml of the ethanol-water mixture of the above concentrations on the center axis of the phosphor conversion LED prepared in Example 6 and the near-infrared probe in the straight line direction. Use a DC power supply to connect the phosphor conversion LED prepared in Example 6, turn on the power supply, and use the near-infrared probe to collect the transmitted light intensity, and collect the transmission spectrum as shown Figure 6 shown.
[0046] See also Figure 5 and Figure 6 , respectively, are the near-infrared transmission spectra of methanol-water mixtures and ethanol-water mixtures of different concentrations under the irradiation of the phosphor conversion LED prepared in Example 6 of the present invention. The results show that under the irradiation of the phosphor conversion LED prepared in Example 6 of the present invention, with the increase of the concentration of pure water in the methanol-water mixture or the ethanol-water mixture, an obvious depression is formed in the 925nm-1025nm band, especially at the OH bond absorption band (980nm), it can be significantly observed that the intensity of the transmitted light decreases with the increase of the concentration of pure water.
Claims
1. A chromium ion-doped phosphate photoluminescent material, characterized in that: The chemical formula is CaHf 4-x (PO4)6:xCr 3+ , 0<x≤0.
09.
2. The method for preparing a chromium ion-doped phosphate photoluminescent material according to claim 1, characterized in that: The following steps are included in sequence: A calcium-containing compound, a hafnium-containing compound, ammonium dihydrogen phosphate and a chromium-containing compound are mixed, calcined at 1150° C. to 1350° C. for 4 to 6 hours in an air atmosphere, and the calcined product is naturally cooled and then ground to obtain a chromium ion-doped phosphate photoluminescent material. A chromium ion-doped phosphate photoluminescent material is obtained; The molar ratio of the calcium-containing compound, the hafnium-containing compound, the ammonium dihydrogen phosphate and the chromium-containing compound is 1:3.91-3.99:6:0.01-0.
09.
3. The method for preparing a chromium ion-doped phosphate photoluminescent material according to claim 2, characterized in that: The calcination temperature is 1230°C to 1280°C.
4. The method for preparing a chromium ion-doped phosphate photoluminescent material according to claim 2, characterized in that: The calcination time is 5 hours.
5. The method for preparing a chromium ion-doped phosphate photoluminescent material according to claim 2, characterized in that: The molar ratio of the calcium-containing compound, the hafnium-containing compound, the ammonium dihydrogen phosphate and the chromium-containing compound is 1:3.95-3.99:6:0.03-0.
07.
6. The method for preparing a chromium ion-doped phosphate photoluminescent material according to claim 2, characterized in that: The calcium-containing compound is calcium carbonate; the hafnium-containing compound is hafnium oxide; and the chromium-containing compound is chromium oxide.
7. The method for preparing a chromium ion-doped phosphate photoluminescent material according to claim 2, characterized in that: After the calcium-containing compound, hafnium-containing compound, ammonium dihydrogen phosphate and chromium-containing compound are mixed and before the calcination in air atmosphere, the process further comprises: grinding the mixture obtained by mixing the calcium-containing compound, hafnium-containing compound, ammonium dihydrogen phosphate and chromium-containing compound to obtain a uniform mixed solid powder.
8. The method for preparing a chromium ion-doped phosphate photoluminescent material according to claim 2, It is characterized in that The calcination is carried out at a heating rate of 5°C / min to 8°C / min.
9. A phosphor conversion LED prepared by combining the chromium ion doped phosphate photoluminescent material as claimed in claim 1 with a blue light LED chip is used to detect the water content in an organic solvent.
10. A phosphor-converted LED of a luminescent material, characterized in that: Weigh the epoxy resin and the CaHf as claimed in claim 1 in a mass ratio of 2:
1. 3.95 (PO4)6:0.05Cr 3+ The compound was placed in a stirrer and mixed for 10 minutes to obtain a uniform phosphor silica gel mixture; the obtained mixture was evenly coated on the surface of the blue light LED chip with a dispenser, the coated blue light LED chip was placed in an oven, the temperature was increased to 100°C at a heating rate of 2°C / min, and the mixture was kept warm for 1 hour in an air atmosphere for curing, and after cooling to room temperature, a CaHf 3.95 (PO4)6:0.05Cr 3+ Phosphor conversion LED with compound as luminescent material.
Citation Information
Patent Citations
Manganese-chromium-codoped alkaline earth titanium phosphate light-emitting thin film as well as preparation method and application thereof
CN103805189A
Luminescent material, preparation method thereof and LED light source
CN116875308A